APLIKASI QUIZIZZ SEBAGAI MEDIA PEMBELAJARAN UNTUK MENINGKATKAN MOTIVASI BELAJAR SISWA - Zuri Astari (SOSPENDIS : Sosiologi Pendidikan dan Pendidikan IPS, 2023)
Industrial revolution 4.0 has brought significant changes to education in Indonesia. Advances in technology are causing changes in the methods and strategies used by teachers in teaching and learning activities in the classroom. The age when the teacher was the source of learning in general, but is now replaced by information that can be obtained from anywhere through fast internet access. Teachers who were initiators are now facilitators who have to constantly develop learning methods and strategies, especially to respond to the changing times. Currently there are many applications available that can be used in the learning phase. One of them is developed as a suggested test/quiz that can be used to find out how well students understand the material taught. From the various educational applications based on quizzes available, one of the learning media that has different and advantages ways to support learning is the Quizizz application. Quizizz is an educational application, which makes the learning process in the classroom more interactive and fun so that it can increase students' motivation to learn